Multimodal Product Promotion: Bridging ESP Learning and Descriptive Speaking Proficiency - Elisanti Agustina (Universitas Islam Negeri Palopo, 2025)
This study examined the effectiveness of multimodal product promotion as a pedagogical strategy to enhance English as a Foreign Language (EFL) students’ descriptive speaking performance. Specifically, third-semester culinary students enrolled in an English for Culinary course at a private university in Surabaya participated in the research. A quasi-experimental design was employed, with 43 third-semester culinary students were randomly assigned to an experimental group (n=22) and a control group (n=21), in which the experimental group received instruction integrating multimodal product promotion tasks, while the control group received conventional speaking instruction. Students' descriptive speaking performance was evaluated using a validated analytic rubric that included fluency, vocabulary, grammar, pronunciation, and content from reliable experts, and the posttest data were analyzed using an independent samples t-test. The findings revealed a statistically significant difference between the two groups, with the experimental group achieving higher mean scores than the control group, t(47) = 5.63, p < .001, a mean difference of 10.10 points, and a large effect size (Cohen’s d = 1.62). These results highlight the pedagogical potential of multimodal learning tasks in promoting oral proficiency, suggesting that integrating real-world, performance-based activities into ESP instruction can meaningfully advance students’ communicative competence.